2019
DOI: 10.1021/acs.jpcb.9b03919
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Liquid Equilibria of 1-Ethyl-3-methylimidazolium Triflate (C2mimTfO) and n-Alkyl Alcohol Mixtures

Abstract: The isobaric vapor liquid equilibria (VLE) of different binary mixtures of the ionic liquid (IL) 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (C2mimTfO) with the n-alkyl alcohols, methanol, ethanol, propan-1-ol, and butan-1-ol, are studied at the pressures of p = 500, 700, and 1000 mbar, covering a composition range 0.25–0.35 ≤ x(solvent) ≤ 1.0. Complementarily, the experimental results are compared with calculations by the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 106 publications
4
27
2
Order By: Relevance
“…Special care was required for the measurements at low temperatures because the influence of the kinetic hindrance of phase separation may become a significant source of error as the viscosity of the samples rises up to high values in the vicinity of a solidifying point. Chemical stability is sometimes a problem for measurements of phase diagrams as well. ,,, In the present study, no signs of decomposition or chemical reaction were observed in any of the systems even at the highest temperatures considered.…”
Section: Methodssupporting
confidence: 40%
See 2 more Smart Citations
“…Special care was required for the measurements at low temperatures because the influence of the kinetic hindrance of phase separation may become a significant source of error as the viscosity of the samples rises up to high values in the vicinity of a solidifying point. Chemical stability is sometimes a problem for measurements of phase diagrams as well. ,,, In the present study, no signs of decomposition or chemical reaction were observed in any of the systems even at the highest temperatures considered.…”
Section: Methodssupporting
confidence: 40%
“…Chemical stability is sometimes a problem for measurements of phase diagrams as well. 51,57,60,61 In the present study, no signs of decomposition or chemical reaction were observed in any of the systems even at the highest temperatures considered.…”
Section: ■ Introductioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In addition, the structure−property relations for the binary mixtures of the C x mimTfO (x = 2, 4, 6) ILs and n-alkyl alcohols (C n OH; n = 1−4) are derived on the basis of this work and previously obtained data. 43,44 ■ EXPERIMENTAL SECTION Materials and Sample Preparation. The IL 1-hexyl-3methylimidazolium trifluoromethanesulfonate (depicted in Figure 1) and the four n-alkyl alcohols methanol, ethanol, propan-1-ol, and butan-1-ol are of commercial origin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They were purified and handled following a standard procedure, which is described in detail in our previous works. 27,28,43,44,144 The ionic liquid was degassed and dried under reduced pressure conditions (p < 1 × 10 −2 mbar) at a temperature of T = 308 K for a minimum of t = 24 h. After this time, the loss of mass detected by weighing was less than 10 −3 g when considering a sample containing 20 g of IL. The n-alkyl alcohols methanol and ethanol were used as received without further purification.…”
Section: ■ Introductionmentioning
confidence: 99%